2020
DOI: 10.4103/tp.tp_68_19
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in malaria patients from an arid region of Western Rajasthan (India)

Abstract: Context: The arid climate of Western Rajasthan is challenging for malaria transmission, with the number of cases correlating directly with the annual rainfall pattern. Moreover, >90% of the cases in this region are caused by Plasmodium vivax , which has recently been shown to cause a similar degree of thrombocytopenia as Plasmodium falciparum . Aims and Objectives: The aim of the study was to determine the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Patients with malaria with volatile malaria epidemiology were analysed for their levels of thrombocytopenia and its associations with different species of malaria in a study conducted by Bansal et al 16 Between August 2017 and October 2018, all patients with microbiologically confirmed malaria and a reported platelet count were included in a retrospective analysis. Rapid diagnostic tests and analysis of blood films helped establish the microbiological diagnosis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patients with malaria with volatile malaria epidemiology were analysed for their levels of thrombocytopenia and its associations with different species of malaria in a study conducted by Bansal et al 16 Between August 2017 and October 2018, all patients with microbiologically confirmed malaria and a reported platelet count were included in a retrospective analysis. Rapid diagnostic tests and analysis of blood films helped establish the microbiological diagnosis.…”
Section: Literature Reviewmentioning
confidence: 99%